Тhe content of essential microelements in growth retarded children organism, depending on the short stature degree - Пахомова, Вікторія Геннадіївна; Большова, Олена Василівна (ScienceRise: Medical Science, 2016)
Children and teenagers short stature is associated with significant imbalance of essential microelements, in particular, Zinc, Selenium, Manganese, Chromium, and Copper. Aim of research: a complex study of essential microelements content in children organism suffering from short stature, determination of the possible influence of essential microelements deficits on growth retardation degree. Materials and methods. 240 patients were examined: 166 boys (69.2 %) and 74 girls (30.8 %) aged 3 to 18 years (the average age was 9.65±0.17 years). 206 children and teenagers with different forms of short stature were among them: 144 boys (69.9 %) and 62 girls (30.1 %) with the average age 10.06±0.2 years. All short statured patients were divided into three groups depending on growth retardation degree. The content of microelements in hair was determined by X-Ray fluorescence method using «ElvaX–med» (Ukraine) spectrometer and method for determination of chemical elements mass fraction in hair (МВВ 081/12–450200 method), certified by Ukrainian State Committee of Standardization, Metrology and Certification (Certificate from June, 14, 2007) and proved by the State Sanitary and Epidemiological Service of Ukraine (Resolution №19 from December, 09, 2008). The content of microelements (Zinc, Selenium, Manganese, Chromium, and Copper) in blood plasma was determined by X-Ray fluorescence method using «ElvaX–med» (Ukraine) spectrometer using method of chemical elements measurement in plasma (МВВ 081/12-0468-07), certified by Ukrainian State Committee of Standardization, Metrology and Certification (Certificate from October, 12, 2007) and proved by the State Sanitary and Epidemiological Service of Ukraine (Resolution №8 from October, 05, 2000). Results. A clear correlation between the growth retardation degree and Zinc content in hair of growth retarded children – with an increase of growth retardation the average level of Zinc in hair of growth retarded children significantly decreases. Any significant difference between the Selenium content in both hair and blood plasma in patients with short stature and different degrees of growth retardation wasn’t found. Considerable reduction of Chromium level in hair and plasma of all patients with short stature comparing with the control group independently of growth retardation degree was found, but any difference between Chromium level indexes in hair of patients with different degrees of growth retardation wasn’t determined. Considerable reduction of Copper level in plasma comparing with the control indexes was determined in children with growth retardation ≥2 SD; any significant difference between indexes depending on growth retardation degree wasn’t determined; the lowest indexes of the Copper content in hair were found at growth retardation ≥3 SD. Manganese level in plasma significantly (but not considerably) is reduced in patients with growth retardation ≥2 SD comparing with patients with growth retardation less than 2 SD, and significantly reduced in relation to the control indexes. Conclusion. Essential microelements imbalance was determined in most short statured patients. The most significant misbalance of was found in Zinc indexes in hair of patients